Peran Pendekatan Pembelajaran Mendalam dalam Menumbuhkan Keterampilan Menulis Siswa - Anita Candra Dewi (FKIP UNSULTRA, 2025)
Learning to write is an essential skill in education because it requires students to master not only the technical aspects of language but also critical, reflective, and creative thinking skills. In the context of 21st-century education, a deep learning approach is seen as an effective strategy for developing students' writing skills. This approach focuses on meaningful understanding, connecting ideas, and the ability to analyze and evaluate information, ultimately contributing to the quality of writing. This article presents a literature review exploring the relationship between deep learning and writing skills, covering its principles, implementation, and challenges faced in elementary and secondary education contexts. Recent studies indicate that students who learn through a deep learning approach tend to produce more structured, argumentative, and original writing. This is because they are trained to connect new knowledge with experience, reflect, and construct logical arguments. However, the implementation of deep learning in practice still faces obstacles, such as limited time, teacher capacity, and a learning culture that is still oriented towards memorization. Therefore, this literature review emphasizes the importance of integrating deep learning strategies into the Indonesian language curriculum, particularly in writing, so that students can develop more critical, creative, and contextual literacy skills.